Sectoral differences in downward real wage rigidity: workforce composition, institutions, technology and competition - Philip Du Caju; Catherine Fuss; Ladislav Wintr (Journal for Labour Market Research, 2012)
This paper examines whether differences in wage rigidity across sectors can be explained by differences in workforce composition, wage-bargaining institutions, technology and competition. We rely on a large administrative matched employer-employee dataset for Belgium over the period 1990 - 2002. Our results indicate that downward real wage rigidity is significantly higher for white-collar workers, lower for older workers and decreases with the level of earnings and bonuses. Beyond labour force composition effects, we find that wages are more rigid in sectors with predominant centralised wage-setting at the sector level as opposed to firm-level agreements. Also, more labour-intensive sectors and competitive sectors have more rigid wages.
Keywords: J31; 330; Lohnstarrheit - Determinanten; sektorale Verteilung; Wirtschaftszweige; Reallohn; institutionelle Faktoren; Tarifverhandlungen; Arbeitskräftestruktur; technische Entwicklung; Wettbewerb; Produktionstechnik; Arbeitsintensität; Belgien